State estimation for MISO non-linear systems in controller canonical form - Schwaller, Benoît; Ensminger, Denis; Dresp-Langley, Birgitta; Ragot, José (Zielona Góra: Uniwersytet Zielonogórski)
We propose a new observer where the model, decomposed in generalized canonical form of regulation described by Fliess, is dissociated from the part assuring error correction. The obtained stable exact estimates give direct access to state variables in the form of successive derivatives. The dynamic response of the observer converges exponentially, as long as the nonlinearities are locally of Lipschitz type.
Keywords: non-linear system; state observers; continuous time